Targeted Prevention of COVID-19, a Strategy to Focus on Protecting Potential Victims, Instead of Focusing on Viral Transmission - Govindarajan R (Dove Medical Press, 2020)
Rajaram Govindarajan Department of Operations Management, Innovation and Data Sciences at the ESADE Business School and Govisystem, Barcelona, SpainCorrespondence: Rajaram GovindarajanDepartment of Operations Management, Innovation and Data Sciences at the ESADE Business School and Govisystem, Barcelona, SpainEmail raja@govisystem.orgAbstract: The lockdown strategy used to prevent the spread of COVID-19 (coronavirus disease 2019) has disrupted the global economy. Some countries have started reopening their economies under the threat of a second wave because studies show that only 4% of the population is infected so far and more waves will be needed to achieve herd immunity. Lockdowns have been used with a primary purpose of regulating the demand for healthcare while ignoring the economic consequences. Contrary to the lockdown strategy, some countries such as Brazil have given priority to their economy leading to very high infection and mortality rates. After a first wave of the pandemic, we now know something critically important—those who are likely to become seriously ill and potentially die if SARS-CoV-2 infection is not prevented. That information cannot be ignored in our strategy and is used to control the pandemic. The paper proposes to focus on managing the risk of the virus being transmitted to the vulnerable rather than focusing on controlling all who can potentially transmit it. It argues that only 4% of the global population is at high risk of severe COVID-19 and would require hospital admission if infected. We propose to target this 4% of the population for preventive efforts. Protecting the vulnerable via lockdowns and other measures will be more effective and efficient than locking down the entire population and destroying their economies that are equally critical to life. We hypothesize that such “targeted prevention” strategies are more likely to help achieve our goals: 1) reduce mortality by preventing the infection reaching its potential victims, 2) spend the resources efficiently by knowing the “target” of our preventive efforts, and 3) achieve effective and efficient control of the pandemic without causing disruption to the socio-economic activities until an effective vaccine is available.Keywords: COVID-19, lockdown, targeted prevention, infection control, SARS-CoV-2, coronavirus